2017
DOI: 10.1177/1937586717698812
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Landscapes: The Impact of Centralized and Decentralized Nursing Station Models on the Efficiency of Care

Abstract: Among the factors contributing to caregiver efficiency and satisfaction are nursing station design, an integrated team approach, and the overall physical layout of the space on walkability, allocation of caregiver time, and visibility. However, unit design alone does not solely impact efficiency, suggesting that designers must consider the broader implications of a culture of care and processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 21 publications
2
61
0
Order By: Relevance
“…The results in this study support those from other studies ( Fay et al, 2017 ; Real, Barduch, & Barduch, 2017 ). It appears that nursing unit design and size (particularly if medium or large units) may affect fall rates because some unit design shapes allow less close visual or aural monitoring than others, which is crucial for preventing falls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results in this study support those from other studies ( Fay et al, 2017 ; Real, Barduch, & Barduch, 2017 ). It appears that nursing unit design and size (particularly if medium or large units) may affect fall rates because some unit design shapes allow less close visual or aural monitoring than others, which is crucial for preventing falls.…”
Section: Discussionsupporting
confidence: 93%
“…This result may reflect lower visibility or access to other staff because of the longer straight corridors associated with the cross-shaped units in this study. This finding is similar to those reported by Fay, Carll-White, Schadler, Isaacs, and Real (2017) ; Real et al (2017) ; and Kalisch and Begeny (2005) , who found that visibility of other staff affected communication with each other, and decentralized workstations resulted in less access and less communication. This finding was also similar to that of Hua, Becker, Wurmser, Bliss-Holtz, and Hedges (2012) , who found that a move from a decentralized design to a hybrid design resulted in nurses feeling more isolated with fewer social interactions (i.e., communication).…”
Section: Discussionsupporting
confidence: 90%
“…The close proximity of the medication room to the NS could improve the frequency of communication and efficiency. Previous studies conducted in Western hospitals also found that enclosed spatial layouts were beneficial to improving privacy (Calleja & Forrest, 2011;Zamani, 2019), and when nurses work in close proximity, the likelihood of communication could be increased (Cai & Zimring, 2011;Fay et al, 2017;Zborowsky et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Work information includes work experience (as a nurse or other patient care work), work space design (any particular work space design that could impact the physical factors, such as patient bed, lifting aids (Pheasant and Ergs 1987), flooring (Cham and Redfern 2001), nursing unit layout (Cohen et al 2004;Fay et al 2017)), as well as work organisation factors (Koehoorn et al 2006). Shift work, particularly shifts that occur outside of a traditional 8-h daytime schedule, can have adverse health effects on nursing personnel, both physically and psychologically (He 2013;Samaha et al 2007).…”
Section: Work Informationmentioning
confidence: 99%